Effects of nerve growth factor (NGF) on blood vessels area and expression of the angiogenic factors VEGF and TGFbeta1 in the rat ovary - Bravo Javier A; Lara Hernán E; Julio-Pieper Marcela; Romero Carmen (BMC, 2006)
Abstract Background Angiogenesis is a crucial process in follicular development and luteogenesis. The nerve growth factor (NGF) promotes angiogenesis in various tissues. An impaired production of this neurotrophin has been associated with delayed wound healing. A variety of ovarian functions are regulated by NGF, but its effects on ovarian angiogenesis remain unknown. The aim of this study was to elucidate if NGF modulates 1) the amount of follicular blood vessels and 2) ovarian expression of two angiogenic factors: vascular endothelial growth factor (VEGF) and transforming growth factor beta 1 (TGFbeta1), in the rat ovary. Results In cultured neonatal rat ovaries, NGF increased VEGF mRNA and protein levels, whereas TGFbeta1 expression did not change. Sectioning of the superior ovarian nerve, which increases ovarian NGF protein content, augmented VEGF immunoreactivity and the area of capillary vessels in ovaries of prepubertal rats compared to control ovaries. Conclusion Results indicate that NGF may be important in the maintenance of the follicular and luteal vasculature in adult rodents, either indirectly, by increasing the expression of VEGF in the ovary, or directly via promoting the proliferation of vascular cells. This data suggests that a disruption on NGF regulation could be a component in ovarian disorders related with impaired angiogenesis.